Existing calf management practices and their adoption using the E information module in Uttar Pradesh (Indian Journal of Animal Production and Management, 2024)
Calf management in traditional dairy farming receives less attention as compared to milking animals. Though  calves represents the main source of replacement stock and are important in letdown of milk, they are  the key to a successful dairy enterprise and preserving & maintaining good quality germplasm. Therefore  it is necessary to keep calf alive during the first few weeks of life by providing careful management of the nutrition, health and wellbeing will ensure the calves get off to a good healthy start. Thus the study was planned to assess the existing adoption of calf management practices and change in knowledge level  of farmers after exposure to E-information module in Uttar Pradesh. A total of 160 dairy farmers who  were rearing the dairy animals and having one recently born calves was interviewed to get first-hand information about calf management and were exposed to E-information module containing details about  the scientific calving management practices. The results state that majority (63.38%)of respondents were feeding colostrum but only 1.87 percent used to feed the colostrum within one hour and the concept of preparing and feeding artificial colostrum was not known to the farmers. It was observed that the only 13.75, 19.38, 3.75 and 17.25 percent of respondent in the study area were following deworming, bedding to calf, disbudding and exposure to sunlight. The information module had change the knowledge and  thus mean gain in knowledge was 16.60 percent among the respondents. Thus the utilization of ICT tools  can be effectively used to enhance the knowledge of farmers about scientific calf management practices.
Keywords: Effectiveness; Feedback; Information module; ICTs; Knowledge; Transition period